2019
DOI: 10.31557/apjcp.2019.20.9.2847
|View full text |Cite
|
Sign up to set email alerts
|

Association of Abnormal Pap Smear with Occult Cervical Stromal Invasion in Patients with Endometrial Cancer

Abstract: Objective: The purpose of this study was to determine the association between abnormal preoperative Pap smear results and occult cervical stromal invasion in endometrial cancer patients. Methods: Medical records were reviewed of patients with endometrial cancer who had undergone surgical staging at Srinagarind Hospital. Patients with gross cervical involvement, with an unsatisfactory Pap smear, without available Pap smear results, with no cervical intraepithelial lesion/invasive cervical cancer, or who had pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…In our study, this rate was determined as 12%. Khumthong et al [11] found that only 21% of 238 patients, 30% of whom had type 2 endometrial cancer, showed preoperative cytology abnormality, and this abnormality was an independent risk factor for cervical stromal invasion. In our study, a total of 12.1% cytological abnormalities were found in 423 patients, 18% of whom were non-endometrioid type tumors, and a borderline significance was found between cervical stromal involvement and smear abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, this rate was determined as 12%. Khumthong et al [11] found that only 21% of 238 patients, 30% of whom had type 2 endometrial cancer, showed preoperative cytology abnormality, and this abnormality was an independent risk factor for cervical stromal invasion. In our study, a total of 12.1% cytological abnormalities were found in 423 patients, 18% of whom were non-endometrioid type tumors, and a borderline significance was found between cervical stromal involvement and smear abnormality.…”
Section: Discussionmentioning
confidence: 99%